Variation in nutritive value of fodder maize (Zea mays) genotypes - Singh, Sultan; Katiyar, P K (The Indian Journal of Animal Sciences, 2012)
Genotypes (10) of maize (IG 96-2, -3, -4, -5, -6, -7, -11, -13, -14 and -15) were grown under uniform agronomic and soil conditions. Leaf and stem fractions were separated for each genotype and compared for chemical constituents, IVDMD and in-sacco DM, NDF and ADF disappearance. Leaf had double CP contents than stem fraction among the different genotypes. The CP contents varied from 3.72 to 12.82% in leaf and stem fractions. Organic matter, lignin and NDF, ash contents were higher in stem and leaf fractions, respectively. Leaf showed 8-10 units higher (P